PERANAN RELAWAN PAJAK SAAT PENDAMPINGAN PELAPORAN SPT TAHUNAN ORANG PRIBADI BERBASIS E-FILING DI KPP PRATAMA JAKARTA TAMANSARI - Vieoletta, Callista; Widjaja, Purnamawati Helen (Jurnal Serina Abdimas, 2024)
The Tax Volunteer activities at KPP Pratama Jakarta Tamansari with a one-month duration starting from 1 March 2023 to 31 March 2023, are carried out with the aim of increasing public awareness and understanding regarding tax obligations, especially in filling out and reporting individual Annual Tax Returns via e-filing. Apart from assisting in the filling process, Tax Volunteers also play a role in providing education about taxation and assistance in ratifying the Population Identification Number (NIK) as a Taxpayer Identification Number (NPWP). The benefits of this activity are many, some of which are gaining new experience in the field of taxation as well as training communication skills by providing education about taxation and assisting taxpayers when reporting their Annual Tax Returns via e-filing. This interaction not only increases taxpayer compliance, but also creates an environment that supports the adoption of e-filing which has a positive impact on the efficiency and effectiveness of the reporting process. The results of this research can be used as a basis for designing a more focused strategy for utilizing the role of tax volunteers, with the aim of increasing the success of e-filing based tax reporting in the future.